Repetitive Intermittent Hypoxia and Locomotor Training Enhances Walking Function in Incomplete Spinal Cord Injury Subjects: A Randomized, Triple-Blind, Placebo-Controlled Clinical Trial - Navarrete-Opazo, Angela; Alcayaga, Julio; Sepúlveda, Oscar; Rojas, Enrique; Astudillo, Carolina (Journal of neurotrauma, 2017)
Incomplete spinal cord injuries (iSCI) leave spared synaptic pathways below the level of injury. Intermittent hypoxia (IH) elicits plasticity in the spinal cord and strengthens spared synaptic pathways, expressed as respiratory and somatic functional recovery in experimental animals and humans with iSCI. This study is a randomized, triple-blind, two-arm parallel clinical trial performed in Santiago, Chile. We compared the effects of a 4-week protocol of IH combined with body weight-supported treadmill training (BWSTT), with continuous normoxia (Nx) and BWSTT on 10-meter walk test (10MWT), 6-minute walk test (6MWT), and timed up and go (TUG) test in American Spinal Injury Association C and D individuals with iSCI. Subjects received daily IH (cycling 9%/21% O every 1.5 min, 15 cycles/day) or continuous Nx (21% O ) combined with 45 min BWSTT for 5 consecutive days, followed by IH/Nx 3 × per week (3 × wIH/Nx) for 3 additional weeks. Subjects were assessed at day 5, weekly from weeks 2-4, and at a 2-week follow-up. Daily IH plus BWSTT enhanced walking speed, expressed as decreased 10MWT time at day 5 versus baseline (IH: -10.2 ± 3.0 vs. Nx: -1.7 ± 1.7 sec, p = 0.006), and walking endurance expressed as increased 6MWT distance at day 5 versus baseline (IH: 43.0 ± 10.7 vs. Nx: 6.1 ± 3.4 m, p = 0.012), but not TUG time. Further, 3 × wIH maintained the daily IH-induced walking speed, and enhanced the daily IH-induced walking endurance, which is maintained up to the 2-week follow-up. We conclude that daily IH enhances walking recovery in subjects with iSCI, confirming previous findings. Moreover, 3 × wIH prolonged or enhanced daily IH-induced walking speed and endurance improvements, respectively, up to 5 weeks post-daily IH. Repetitive IH may be a safe and effective therapeutic alternative for persons with iSCI.